Regulation of Algal Bloom Hotspots Under Mega Estuarine Constructions in the Changjiang River Estuary - He, Yanru; Wang, Yihe; Wu, Hui (Frontiers in Marine Science, 2022)
Massive large-scale engineering projects have been built in river estuaries around the world, but their effects on environments in the surrounding coastal waters were less emphasized compared to those due to the watershed projects. In this study, we used the Changjiang River Estuary as an example to show that a significant consequence can be resulted in such a situation. Through analyzing the harmful algal bloom events data and the chlorophyll satellite data, we investigate the spatiotemporal variations of algal blooms in the estuary and its adjacent water. The results indicate that the location of algal bloom hotspot changed over the period of the estuarine constructions. Furthermore, using a well-validated numerical model, we explored the mechanisms responsible for such an ecosystem regime shift. It was found that after the estuarine constructions were built, the surface chlorophyll maximum was attenuated and part of it migrated landward north of the river mouth but was strengthened south of the river mouth and extended seaward. Alternations of the nutrient concentration distribution and turbidity distribution induced by river plume deviation are responsible for the redistribution of the high chlorophyll concentration area. By contrast, the direct impact of the Three Gorges Dam through changing the runoff and sediments flux, which has been highlighted in numerous studies, was less important than expected. Given the fact that Three Gorges Dam and mega estuarine constructions were built in a similar period, any observed regime shift of hydrodynamic and ecological status outside the estuary should be interpreted with particular caution.